Iowa Birdline update, September 19, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for September 19, 1994. Highlights of the update include sightings of a Long-tailed Jaeger, a Cattle Egret, a Peregrine Falcon, and a Red-necked Phalarope. Also of note were observations of eleven shorebird species at Otter Creek Marsh and a count of over a thousand Broad-winged Hawks passing over Grammer Grove Park. Also included are handwritten notes for the next week's update with sightings of Yellow Rails and a Parasitic Jaeger. Epson - sheet feed/flatbed